2005
DOI: 10.1074/jbc.m506551200
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induced by the Kinase Inhibitor BAY 43-9006 in Human Leukemia Cells Involves Down-regulation of Mcl-1 through Inhibition of Translation

Abstract: BAY 43-9006 is a kinase inhibitor that induces apoptosis in a variety of tumor cells. Here we report that treatment with BAY 43-9006 results in marked cytochrome c and AIF release into the cytosol, caspase-9, -8, -7, and -3 activation, and apoptosis in human leukemia cells (U937, Jurkat, and K562). Pronounced apoptosis was also observed in blasts from patients with acute myeloid leukemia. The Ras/Raf/mitogen-activated protein kinase (MEK) 2 /extracellularsignal-regulated kinase (ERK) cascade plays a critical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
250
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(281 citation statements)
references
References 67 publications
30
250
1
Order By: Relevance
“…This critical step is controlled and mediated by the BCL-2 family of proteins [22]. MCL-1, one of the BCL-2 family members that inhibits cytochrome c release and caspase activation, has been shown to be downregulated following sorafenib treatment in a variety of human tumour cell lines [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This critical step is controlled and mediated by the BCL-2 family of proteins [22]. MCL-1, one of the BCL-2 family members that inhibits cytochrome c release and caspase activation, has been shown to be downregulated following sorafenib treatment in a variety of human tumour cell lines [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In more sensitive cell lines, such as Jurkat leukaemia cells or SKMEL5 melanoma cells, sorafenib-induced apoptosis is largely caspase independent because Z-VAD-FMK is not inhibitory and AIF translocation has an essential role in the apoptotic process [23,38]. A previous study observed a higher rate of sorafenib-induced apoptosis than that observed in this study: ∼80% cell death for Jurkat cells at 15 µmol L −1 and 80.9% cell death for SKEML5 cells at 20 µmol L −1 (27.7% cell death was observed for PC-3 cells at 10 µmol L −1 in the current study).…”
Section: Discussionmentioning
confidence: 99%
“…Mcl-1 localizes to the mitochondria and other intracellular membranes and has a relatively short half-life (31). Overexpression of Mcl-1 protects tumor cells from apoptosis induced by diverse agents, including flavopiridol, triptolide, and sorafenib (25,27,43). Mcl-1 is overexpressed in neoplastic cells in hematologic malignancies, including CML and SM (1,44).…”
Section: Discussionmentioning
confidence: 99%
“…cells of the tumour vasculature to inhibit angiogenesis (Wilhelm et al, 2004). Sorafenib also induces apoptosis in several human cancer cell lines (Rahmani et al, 2005;Yu et al, 2005), including melanoma cells (Panka et al, 2006b). Sorafenib downregulates Mcl-1 protein levels in a time-and dose-dependent manner to induce apoptosis in renal, colon and breast tumour lines (Rahmani et al, 2005;Yu et al, 2005).…”
Section: Sd Pdmentioning
confidence: 99%